An Ultrasensitive Gold Nanoband Aptasensor for Mercury(II) Detection in Aquatic Environment. Issue 10 (14th June 2019) - Gan, Ying; Sun, Jiadi; Liang, Tao; Tu, Jiawei; Hu, Ning; Wan, Hao; Wang, Ping
Abstract : Heavy metal contamination in aquatic environment has made great adverse impacts on human health and environment. In this work, a label-free electrochemical gold nanoband aptasensor (GNA) was developed using thymine-Hg 2+ -thymine (T-Hg 2+ -T) coordination chemistry for Hg 2+ detection in drinking water. The gold nanoband sensor contains gold nanoband working electrode with a band thickness of 100 nm. The nanoscale working electrode increases the mass transfer rate and sensitivity for Hg 2+ detection. Moreover, the gold nanoband sensors are cost-effective and can be easily regenerated by cutting the edge after the performance decreases dramatically compared with microelectrodes and disk electrodes. T-rich oligonucleotides modified with thiol group was self-assembled onto the working electrode through Au-S covalent bonding. In the presence of Hg 2+, oligonucleotides will capture Hg 2+, thus inducing the conformational change from single-strand to duplex-like structure that would promote electron transfer. Electrochemical impedance spectroscopy (EIS) was used to detect the Hg 2+ -mediated conformational changes. By optimizing experimental conditions, the linear range of proposed biosensor is from 0.1 nM to 1 μM, and the limit of detection is 40 pM (8 ppt). Furthermore, this nanobiosensors exhibited high selectivity and a great potential to detect trace Hg 2+ in real samples from aquatic environment.